(untitled) (Marketing Journal, 2025)
This article analyzes the issue of increasing regional economic -social opportunities based on the clustering approach. Clustering is considered as an important factor in regional development, and its impact on the local areas of entrepreneurship, industry, agriculture and services is studied. Also, through the effective clustering model, the possibilities of increasing employment levels, attracting 377 investments and forming an innovative environment are considered. The article analyzes the experience of developed countries and gives recommendations for the